Effects of L-carnitine supplementation on lipid profile in adult patients under hemodialysis: a systematic review and meta-analysis of RCTs - Karimi, Mehdi; Pirzad, Samira; Pourfaraji, Seyed Morteza Ali; Parhizkar Roudsari, Peyvand; Shirsalimi, Niyousha; Ahmadizad, Sajad (Frontiers in Medicine, 2024)
Background: Chronic kidney disease (CKD) affects 10% of the global population and leads to end-stage renal disease (ESRD). Hemodialysis is a common treatment for ESRD, but patients often have low carnitine levels, leading to dyslipidemia, a risk factor for cardiovascular disease and the leading cause of mortality. This study aimed to assess the effects of L-carnitine on lipid profiles in adult hemodialysis patients. Methods: A comprehensive search was conducted across the online databases from inception to June 2024 to identify randomized clinical trials (RCTs) evaluating the effects of L-carnitine on lipid profiles in hemodialysis patients. Data extraction and quality assessment were performed, focusing on primary outcomes, including changes in triglycerides (TG), total cholesterol (TC), high-density lipoprotein (HDL), low-density lipoprotein (LDL), and very low-density lipoprotein (VLDL), and secondary outcomes including blood pressure (BP) and body mass index (BMI). Results: A total of 28 RCTs were eligible for the current systematic review, including 1340 hemodialysis patients (671 intervention, 669 control). There were no significant differences in the mean change of TG (SMD: -0.006; 95% CI, -0.272 to 0.259; P = 0.95), TC (SMD: -0.086; 95% CI, -0.253 to -0.079; P = 0.29), HDL (SMD: 0.060; 95% CI, -0.057 to 0.177; P = 0.29), LDL (SMD: -0.075; 95% CI, -0.274 to 0.123; P = 0.43), VLDL (SMD: -0.064; 95% CI, -0.272 to 0.142; P = 0.51), BMI (SMD: -0.025; 95% CI, -0.139 to 0.088; P = 0.56), systolic BP (SMD: 0.055; 95% CI, -0.110 to 0.220; P = 0.43), and diastolic BP (SMD: -0.028; 95% CI, 0.156 to 0.099; P = 0.56). The same insignificant findings were observed after conducting a subgroup analysis based on the route of administration (intravenous vs. Oral). Conclusion: L-carnitine supplementation does not significantly change and improve the serum lipid profile, including TG, TC, HDL, LDL, and VLDL levels. Additionally, it has no notable effects on BMI, systolic, or diastolic BP.